RAÄ-2021-3144 instrument report µXRF in situ - Marei Hacke (Swedish National Heritage Board, 2022)
XRF maps and point analyses carried out by the heritage laboratory from the the Swedish National Heritage Board on two Wari khipus from the Museums of World Culture, Gothenburg, Sweden in the context of project Dnr RAÄ-2021-3144.
Keywords: Wari; khipu; textile; mordant; XRF; dye; camelid; cotton; History and Archaeology; Historia och arkeologi